2022
DOI: 10.3390/medicina58010123
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Urological Complications Associated with Caesarean Section—A Case-Control Study

Abstract: Background and Objectives: Acute urologic complications, including bladder and/or ureteric injury, are rare but known events occurring at the time of caesarean section (CS). Delayed or inadequate management is associated with increased morbidity and poor long-term outcomes. We conducted this study to identify the risk factors for urologic injuries at CS in order to inform obstetricians and patients of the risks and allow management planning to mitigate these risks. Materials and Methods: We reviewed all cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In patients discharged without indwelling urinary catheters, the infection rate was low, although patients were exposed to the same risk of infection in hospital as patients with urinary catheters. In other local studies, we have not reported the occurrence of MDR UTIs in patients discharged without urinary catheters [45]. It is likely that a normal urinary system without a urinary catheter does not develop UTIs despite possible contamination with CR Kpn, which is why we do not suggest screening all discharged patients for MDR UTIs as in other studies [46], but only those patients discharged with urinary catheters, especially if their removal is not expected for a long time.…”
Section: Discussionmentioning
confidence: 68%
“…In patients discharged without indwelling urinary catheters, the infection rate was low, although patients were exposed to the same risk of infection in hospital as patients with urinary catheters. In other local studies, we have not reported the occurrence of MDR UTIs in patients discharged without urinary catheters [45]. It is likely that a normal urinary system without a urinary catheter does not develop UTIs despite possible contamination with CR Kpn, which is why we do not suggest screening all discharged patients for MDR UTIs as in other studies [46], but only those patients discharged with urinary catheters, especially if their removal is not expected for a long time.…”
Section: Discussionmentioning
confidence: 68%
“…The administration of multiple ESWL sessions prolongs the time to achieve stone-free status and thus increases the risk of reflux, pyelonephritis, and double-J syndrome, as emphasized in other studies [ 13 , 27 - 29 ]. Reflux pyelonephritis can be a serious complication that can quickly lead to urosepsis in the absence of adequate antibiotic treatment [ 30 ]. However, as in other studies [ 28 , 31 ], the incidence of symptoms associated with double-J catheters in our study was much lower than the nearly 80% reported in other studies [ 13 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bladder injuries are usually recognized and addressed intraoperatively, but this may not always be possible (4), and there exists the possibility of diagnosis and intervention in the early period after the CS.…”
Section: Introductionmentioning
confidence: 99%